The activity of the Mamy Głos Foundation in the context of youth political activism - Pająk-Patkowska, Beata (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
This paper aims to examine the activity of the Mamy Głos Foundation [We have a voice], an organization founded in 2015 by junior high school students from a handful of towns in Poland. For this purpose, a review of available materials about this organization will be carried out and information will be collected using in-depth interviews with the founders of the organization. The main research question concerns the motivation behind young people’s activity in the foundation, the methods used to achieve the goals of the organization and its founders’ profiles. Their activity will be presented in the context of political activism among young people, including gender differentiation.

Celem artykułu jest analiza działalności podejmowanej przez fundację Mamy Głos, organizację założoną w 2015 r. przez gimnazjalistki z kilku polskich miast. Posłużą do tego dostępne materiały dotyczące tej organizacji, a także dane zebrane za pomocą wywiadu pogłębionego przeprowadzonego z założycielkami organizacji. Główne pytania badawcze dotyczą motywów aktywności podejmowanej w ramach Mamy Głos, sposobów realizacji zakładanych przez organizację celów, charakterystyki założycielek. Działalność ta zostanie przedstawiona w kontekście aktywności politycznej młodzieży, z uwzględnieniem płci.
Aktywność fundacji Mamy Głos w kontekście aktywności politycznej młodych
Keywords: youth; Mamy Głos Foundation; political activism; młodzież; Fundacja Mamy Głos; aktywność polityczna